Efficacy of Commercially Available Anthelmintics in Controlling Gastrointestinal Nematodes in Goats Managed Under Natural Conditions in the South Western Highlands of Uganda - Benda, Katali Kirungi; Ampaire, Andrew; Komungyeyo, Jenninah; Mukiibi, Robert; Masembe, Charles; Onzima, Robert (American Journal of Clinical and Experimental Medicine, 2015)
Goat production is of great importance especially to the rural farmers in Uganda, serving a number of socioeconomic functions. Among the limitations of goat production in Uganda are Gastro Intestinal Nematodes (GINs). These are usually controlled using commercial Anthelmintic compounds. Due to continual improper usage of these drugs by the farmers, evolution of resistant strains has resulted thus affecting their effectiveness in controlling the GINs. The aim of this study was to determine the efficacy of four commercially available anthelmintics used for controlling Gastro Intestinal Nematodes (GINs) in goats on natural pastures in the south western highlands of Uganda. A mini survey was conducted prior to the current study to get information about the most commonly used anthelmintics in the study area. Initially, 240 goats were enrolled into the study and, 210 were used in the final analysis. The goats were randomly allocated to 5 different treatment groups at district level namely; untreated controls (CTRL), Albendazole 10% (ABZ), Ivermectin (IVE), Levamisole (LEV) and Closantel (CL). Faecal and blood samples were collected from each animal at 0, 14, 28 and 42 days post-treatment respectively and analysed for faecal egg counts (FEC) using the modified McMaster method. The percentage reduction, FECR % was calculated from the arithmetic mean and difference in FEC between breeds, district and age were assessed by univariate analysis of variance in SPSS. Results at day zero indicated that age and district had significant effect on FEC (P-value= 0.001 and 0.035respectively) while breed had no significant effect (P-value=0.465). At 14 days post-treatment, district, breed and treatment had significant effects on FEC (P-value=0.00, 0.02 and 0.05 respectively) while age was not (P=0.931). Albendazole and Levamizol were the most used drugs in the study area while Closantel and Ivermectin were the least used. Drug efficacy varied between districts, with the highest mean Fecal Egg Count Reduction (FECR) achieved with Closantel (FECR%=100%), while the lowest mean FECR observed with Albendazole (FECR%=49%) in Rukungiri and Kisoro districts respectively. Ivermectin was effective in all the four districts (FECRT% > 95%). Our study confirmed presence of Anthelmintic resistance (AR) by GIN in goats in the south western highlands of Uganda. Closantel is highly effective against GINs, but albendazole is not due to its wide spread usage. Further research is necessary to find and validate alternative strategies for the control of GINs in goats.